2019
DOI: 10.3389/fmicb.2019.00463
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Products From Plant-Endophytic Gram-Positive Bacteria

Abstract: Endophytes constitute plant-colonizing microorganisms in a mutualistic symbiosis relationship. They are found in most ecosystems reducing plant crops’ biotic and abiotic stressors by stimulating immune responses, excluding plant pathogens by niche competition, and participating in antioxidant activities and phenylpropanoid metabolism, whose activation produces plant defense, structural support, and survival molecules. In fact, metabolomic studies have demonstrated that endophyte genes associated to specific me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(90 citation statements)
references
References 120 publications
(118 reference statements)
1
77
0
3
Order By: Relevance
“…subtilis (EPP65), and B. cereus (EPP5, EPP71, and EPP74) strains are highly promising and proficient antagonists showing ≥ 50% fungal mycelium growth inhibition against all the tested phytopathogenic fungi (RS, SR, and FS). One of the most significant characters of these endophytic bacterial strains reflecting strong antagonistic behavior may be explained by prevalence of structurally different antibiotics (surfactin, bacillomycin, and iturin) with manifold mode of action [14,21,26,[68][69][70]. PCR based screening of AMP gene(s) in the present study clearly reflected the presence srfA, bmyC, and ituD genes in all the endophytic Bacillus strains.…”
Section: Discussionsupporting
confidence: 50%
“…subtilis (EPP65), and B. cereus (EPP5, EPP71, and EPP74) strains are highly promising and proficient antagonists showing ≥ 50% fungal mycelium growth inhibition against all the tested phytopathogenic fungi (RS, SR, and FS). One of the most significant characters of these endophytic bacterial strains reflecting strong antagonistic behavior may be explained by prevalence of structurally different antibiotics (surfactin, bacillomycin, and iturin) with manifold mode of action [14,21,26,[68][69][70]. PCR based screening of AMP gene(s) in the present study clearly reflected the presence srfA, bmyC, and ituD genes in all the endophytic Bacillus strains.…”
Section: Discussionsupporting
confidence: 50%
“…Endophytic Bacillus produces phytohormones such as abscisic acid, auxins, brassinosteroids, cytokinins, ethylene, gibberellins, jasmonates, and strigolactones, and increases nutrient (nitrogen and phosphorous) accessibility to the host (Reinhold-Hurek and Hurek 2011;Brader et al 2014;Santoyo et al 2016;Shahzad et al 2016;Ek-Ramos et al 2019). Zeiller et al (2015) reported that C. botulinum 2301 significantly produce PGPs in a field experiment of clover.…”
Section: Ramularia Endophyllamentioning
confidence: 99%
“…Endofit dari kelompok Streptomyces, Kenedia nigriscans strain NRRL 30562 dan Streptomyces caeruleatus dilaporkan efektif terhadap patogen kedelai Xanthomonas campestris pv. glisin [28] , sedangkan metabolit dari tanaman Azadirachta indica dan Nothofagus spp adalah endofit actinomycetes yang dapat menghambat jamur patogen tanaman Mycosphaerella fijiensis, Sclerotinia sclerotiorum, dan Rhizoctonia solani, dan Pythium sp dan Phytophthora [29] , juga metabolit sekunder yang dihasilkan oleh actinobacteria terbukti menghasilkan aktivitas antimikroba dan antitumor, berguna dalam bidang pertanian, kedokteran, dan kedokteran hewan [30] . Keanekaragaman endofit yang tinggi, produksi metabolit, dan adaptasinya terhadap kondisi stres sehingga dapat dijadikan sumber metabolit baru untuk mengurangi penggunaan bahan kimia pertanian dalam produksi makanan dan obatobatan maupun di bidang proteksi tanaman kehutanan.…”
Section: Uji Antagonis Bakteri Endofit Asalunclassified